Pemetaan sebaran dan deskripsi potensi obyek Wisata Umbul di Kabupaten Klaten - Kunthum Ria Anggraheny; Nevy Farista Aristin; Norma Yuni Kartika (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
Tourism is an important sector in improving the economy of a region. Klaten Regency is known as 1001 umbul regency, of which the umbul tourism object is spread over 26 districts. This study aims to identify the distribution and potential of umbul tourism objects in Klaten Regency. This research is a quantitative approach with survei method, using spatial analysis, namely GIS and analysis of scoring and classification. Based on the results of this study, the distribution of umbul tourism objects in Klaten Regency is spread over seven districts, which form a straight line and are still in one aquifer network. The internal potential have high value, namely Umbul Brintik, Susuhan, Pelem, and Ponggok. The high external factors are owned by Umbul Susuhan,Ponggok, and Pelem. The potential for a combination of internal and external factors with a high value is owned by Umbul Brinta, Susuhan, Pelem, and Ponggok. Umbul Gedaren and Jolotundo still have moderate potential. Umbul Gedaren and Jolotundo still need to improve every element in internal and external factors so that these two tourism objects can be develop optimally. The potential of this umbul tourism object, if it is developed optimally, will later be useful for the people around the tour which can later improve the economy and welfare of the community. DOI: http://dx.doi.org/10.17977/um022v5i22020p79